PROPOSAL FOR A CYCLOVY IN THE CANTÓN GUANO, CHIMBORAZO PROVINCE - Palaguachi Sumba, Juan Pablo; Villa Uvidia, Ruffo Neptalí; Guerra Sarche, Xavier Alejandro; Barahona Chavarrea, Paul Eduardo (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
This project emerges from the necessity of encourage sustainable means of transport such as bicycle systems, which cover the growing exponential tendency of the demand that faces   the limitations of a traditional linear supply. Biking attempts to reduce pollution which is an imperative trouble to solve in many cities worldwide, caused mainly because of motorized vehicles. Guano was selected as an appropriate scenario for this project due to its geographical conditions, walking as one of the main choices in modal split, and its tourism potential. Current mobility and infrastructure situation have been assessed, also several technical parameters for bike lane construction have been synthetized to finally make a concrete proposal. The results address to a low people percentage that use bicycle as a main transport mode, because of the insecure biking conditions. Also, it is remarkable the high acceptance percentage, approximately 40% of people who are willing to ride their bike if there is an appropriate bicycle lane. In conclusion, the project consists of 11.5 km of biking lane whit an adequate signaling system and all the security guarantees for the users, which crosses the longitudinal axis of the urban area of Guano.